Understanding the relevance of farmers' markets from 1955 to 2022: A bibliometric review - Áron Török; Sándor Kovács; Gréta Maró; Zalán Márk Maró (Journal of Agriculture and Food Research, 2024)
With the emergence of modern food supply chains, there has been a noticeable decline in consumer trust and an increase in information asymmetry. Short food supply chains, including farmers' markets, offer potential solutions to these issues. Currently, farmers' markets are primarily found in the United States and the European Union, and their impact on sustainability has gained significant attention. However, the relevance of this traditional approach within modern supply chains remains largely unexplored. Thus, this study aims to examine the existing literature on farmers' markets using bibliometric techniques applied to 1765 documents sourced from the Scopus and Web of Science databases spanning from 1955 to 2022. The paper tracks the research trends associated with farmers' markets by identifying the stages of evolution of key topics, articles, journals, author citations, and co-citation networks. The findings demonstrate an increasing trend in publication of papers on this subject, highlight five interconnected areas of market research, and provide a foundation for future research and policy making by outlining the main and specific research avenues to explore.